The Influence of Work Environment and Employee Competency on Employee Performance Mediated by Motivation - Goh, Joan; Sentoso, Antony; Setyawan, Agustinus (UMSurabaya Publishing, 2024)
This research aimed to find out how the work environment and employee competence influence the performance of employees who work at the People's Credit Bank or BPR Batam City by using motivation variables as mediation. The research used a population of 5 BPRs, ranked 1 to 5, regarding the profit and loss of all BPRs in Batam City. From this population, 210 samples were taken. The sampling technique that will be used is proportionate stratified random sampling or samples taken randomly from a population that is not homogeneous and proportionally stratified, and the research data analysis method used is Partial Least Square (PLS) using SmartPLS software. The research results show that the work environment and employee competence influence the mediating variables, namely motivation, and motivation also positively influences employee performance. Then, the results further show that the work environment and employee competence do not significantly influence employee performance. The limitation experienced when conducting research is that the population taken is limited to BPR employees in Batam City, and other variables can still influence the research results.